Efficacy of formulated feeds for juvenile green-back grey mullet Liza subviridis (Valenciennes) - Das, N G; Bhattacherjee, H; Khan, M I (Indian Journal of Fisheries, 2011)
The culture practice of green-back grey mullet Liza subviridis is becoming popqlar. But no work has been conducted on feed formulation for this species. This study shows the effect of protein levels, protein sources and the natural planktonic food on the growth and survival of the species.